PENGUATAN MANAJEMEN BISNIS UMKM BERBASIS DIGITAL UNTUK MENINGKATKAN DAYA SAING PRODUK LOKAL BAGI PELAKU USAHA UMKM DI KECAMATAN LANDONO - Windayani Windayani; Triwulandari Nehru Putri; Sri Wiyati Mahrani; Ghalib Suprianto (Jurnal Pengabdian Masyarakat Berkelanjutan, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in enhancing regional economic development. However, MSME actors in Landono District still face various challenges, particularly limited understanding of business management and the utilization of digital technology in product marketing. This Community Service program aimed to strengthen the capacity of MSME actors through digital-based business management training to improve the competitiveness of local products. The implementation methods included socialization, training, mentoring, and evaluation. The materials provided covered business management, simple financial record-keeping, digital marketing strategies, and the use of social media and marketplaces. The results of the activity indicated an improvement in participants’ knowledge and skills in managing their businesses and marketing products digitally. MSME actors began to implement simple financial records and utilize digital platforms for product promotion. This program had a positive impact on increasing entrepreneurs’ self-confidence and opening opportunities for market expansion. Therefore, strengthening digital-based business management has proven to be an effective strategy for enhancing the competitiveness of local MSME products in Landono District.